Stability and complexity in model meta-ecosystems - Dominique Gravel (Nature Portfolio, 2016)
The mechanisms allowing highly biodiverse ecosystems to remain stable are poorly understood. Here, Gravel and colleagues provide theoretical evidence that dispersal of organisms and material modifies species interactions and thus enables highly biodiverse communities to exist.